(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The Riovariatm Andijan branch analyzed the 70 patients who were on account" D "with the diagnosis of" colon cancer " following chemotherapy and chronochemotherapy. In 80-90% of patients receiving chemotherapy, different manifestations of side effects are observed. The observation of these toxic complications is explained by the effect of the cytostatic drug on typical cells.